Analysis to Realize Competitive Advantage Through Education Management - Hasibuan, Havidah Adawiyah; Putri, Tiara Zakiah; Harahab, Ahmad Rifai; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
This research focuses on the study of management in educational leadership at school organizational levels. The aim is to analyze all leadership management indicators that determine school excellence. This research uses a library research method where researchers collect relevant data from books, journals, dissertations, theses and theses without conducting a field survey. Then the results of data collection were analyzed for suitability of the research topics and themes to the theme of this research. The results of the analysis show that leadership management indicators for realizing school excellence include aspects of organization, learning, human resources and infrastructure, and organizational culture.